Australindolones, New Aminopyrimidine Substituted Indolone Alkaloids from an Antarctic Tunicate Synoicum sp. - Sofia Kokkaliari; Kim Pham; Nargess Shahbazi; Laurent Calcul; Lukasz Wojtas; Nerida G. Wilson; Alexander D. Crawford; Bill J. Baker (Marine Drugs, 2022)
Five new alkaloids have been isolated from the lipophilic extract of the Antarctic tunicate Synoicum sp. Deep-sea specimens of Synoicum sp. were collected during a 2011 cruise of the R/V Nathanial B. Palmer to the southern Scotia Arc, Antarctica. Crude extracts from the invertebrates obtained during the cruise were screened in a zebrafish-based phenotypic assay. The Synoicum sp. extract induced embryonic dysmorphology characterized by axis truncation, leading to the isolation of aminopyrimidine substituted indolone (1–4) and indole (5–12) alkaloids. While the primary bioactivity tracked with previously reported meridianins A–G (5–11), further investigation resulted in the isolation and characterization of australindolones A–D (1–4) and the previously unreported meridianin H (12).